Integral-field kinematics and stellar populations of early-type galaxies out to three half-light radii - Boardman, N; Weijmans, A; van den Bosch, R; Kuntschner, H; Emsellem, E; Cappellari, M; de Zeeuw, T; Falcón-Barroso, J; Krajnović, D; McDermid, R; Naab, T; van de Ven, G; et al. (Oxford University Press, 2017)
We observed 12 nearby HI-detected early-type galaxies (ETGs) of stellar mass ∼10^10M⊙ ≤ M∗ ≤ ∼10^11 M⊙ with the Mitchell Integral-Field Spectrograph, reaching approximately three half-light radii in most cases. We extracted line-of-sight velocity distributions for the stellar and gaseous components. We find little evidence of transitions in the stellar kinematics of the galaxies in our sample beyond the central effective radius, with centrally fast-rotating galaxies remaining fast-rotating and centrally slow-rotating galaxies likewise remaining slow-rotating. This is consistent with these galaxies having not experienced late dry major mergers; however, several of our objects have ionized gas that is misaligned with respect to their stars, suggesting some kind of past interaction. We extract Lick index measurements of the commonly used Hβ, Fe5015, Mgb, Fe5270 and Fe5335 absorption features, and we find most galaxies to have flat Hβ gradients and negative Mgb gradients. We measure gradients of age, metallicity and abundance ratio for our galaxies using spectral fitting, and for the majority of our galaxies find negative age and metallicity gradients.We also find the stellar mass-to-light ratios to decrease with radius for most of the galaxies in our sample. Our results are consistent with a view in which intermediate-mass ETGs experience mostly quiet evolutionary histories, but in which many have experienced some kind of gaseous interaction in recent times.